Experimental study on effects of superfeed pressure of economizer on twin-screw refrigeration compressor performance - 吴华根; 彭学院; 邢子文; 束鹏程 (Zhileng xuebao)
The capacity of the refrigeration system could be increased by using the economizer, but the COP would not be improved equally due to the increased compressor power consumption from super feeding, and the improvement of COP depends mainly upon the parameters such as superfeed pressure, superfeed port location. In this study, the thermodynamic processes of the twin-screw refrigeration compressor at different superfeed pressures were investigated by analyzing the indication diagrams recorded in the twin-screw refrigeration compressor with an economizer, and the influence of the super-feed pressure on the compressor efficiency and system COP was obtained. The results show that the gas pressure in working chamber experiences a rapid increase as super-feed gas enters the chamber, and then a slow rise, and finally the pressure has a slight drop at the late phase of the super-feeding process. Correspondingly, the compressor efficiency and COP rise first and then drop, depending upon the superfeed pressure. As a result, there is an optimum superfeed pressure under which the system COP reaches the best.